تقويم أداء المديرية العامة للتخطيط وضبط الجودة بوزارة التربية والتعليم بسلطنة عمان في ضوء معايير نموزج التميز الأوروبي( EFQM ) - Abdullah Hamad Said Al-Mashari (Universiti Sains Islam Malaysia, 2024)
This study evaluated the performance of the Directorate General of Planning and Quality Control, the Ministry of Education in the Sultanate of Oman in light of the standards of the European Excellence Model (EFQM). The study aimed at evaluating the performance of the Directorate by identifying the level of applying the standards of the European Excellence Model in the performance of the Directorate. The study applied descriptive analysis method by describing and analysing the level of performance of the Directorate in the light of the criteria of the European Excellence Model. Using two questionnaires which have been designed by the researcher to measure the extent to which the criteria for the European model of excellenge were applied in the Directorate. The second questionnaire was used to measure the application of the results criteria to the European excellence Model in the Directorate, the two samples were applied to the sample of the study(302 individuals). They comprised of human resources in the Directorate General of Planning and Quality Control in the Ministry as well as from their counterparts in the educational departments. The researcher used the SPSS program to analyse the data. The study has concluded that the level of the overall application level of the standards of the European Excellence Model in the performance of the Directorate General of Planning and Quality Control reached a limited level. Thus, the applicability of the standards parameters (leadership, human resources, strategy, partnerships and resources, processes, services and products) are at a medium average level. This level of all possible standards, excluding the HR standard, was limited at the application level. With regard to implication on standards (implications on the beneficiaries, implications on the human resources, implications on society as well as implications on main performance) were all at a limited level of application. In the light of the study results.